Evaluation of media for sporangial production and radial growth of Phytophthora cactorum - Fortes, Joel Figueiredo; Pecknold, Paul C. (Pesquisa Agropecuaria Brasileira, 2014)
Six media were compared for sporangial production and radial growth of Phytophthora cactorum (Lebert & Cohn) Schroeter. The media included: frozen lima bean agar (FLB), clarified V-8 juice agar (V-8 juice), fresh potato dextrose agar (PDA), Difco corn meal agar (DCM), Difco lima bean agar (DLB), and a semi-synthetic medium (GN) containing salts, thiamine, glucose and nitrate. Sporangial production was greatest on FLB, followed by V-8 juice; all isolates consistently produced more sporangia on these two media than on the other media tested. Sporangial production was substantially less on DCM, while DLB, PDA, and GN gave very poor sporangial production. The best radial growth occurred on DLB, followed by V-8 juice, FLB, DCM, PDA, and GN, respectively. There was no significant difference in radial growth on V-8 juice and DLB, nor on V-8 juice and FLB; however, growth was significantly less (P=0.05) on all other media.